Urban Anthropology: The MENA Region (Middle East and North Africa) - (:unkn) unknown (My University, 2021)
With massive urbanization across the MENA (Middle East and North Africa) region over recent decades, research in urban anthropology has intensified. During the 1970s intense population growth (demographic transition) and rural-to-urban migration attracted the attention of many anthropologists who studied the ruralization of the city and its capacity to integrate newcomers. Anthropologists (and geographers) addressed this concern by focusing on urban practices, especially those taking place on the margins of the city. Today, urban anthropology has become one of the most important empirical and analytical prisms for observing MENA societies. The main achievements and paradigms of urban anthropology in the MENA region are structured along three axes: urbanity and urban practices, public spaces, and urban culture.
Keywords: African Research